'Interoperability of the Mind': Professional Military Education and the Development of Interoperability. Issue 4 (3rd July 2016) - Paget, Steven
Abstract : The prevalence of coalition operations has ensured that interoperability between multinational forces is of overarching importance. Although historically interoperability was mainly seen as a matter of technology, Steven Paget argues that cultural interoperability is just as, if not more, significant. Cultural interoperability can be developed in many ways, but exchanges of international students and teachers during the process of professional military education has the potential to redress negative stereotypes, solidify strong existing bonds and enhance interoperability. As a considerable number of international exchange officers at professional military education institutions progress to the highest ranks of their own armed forces, the potential long-term benefits are vast.